American legislative leaders in the Midwest, 1911-1994 - Sharp, Nancy Weatherly; Sharp, James Roger, 1936- (Greenwood Press, 1997)
A biographical dictionary of state house speakers from 1911 to 1994, this book covers speakers from Illinois, Indiana, Iowa, Kansas, Michigan, Minnesota, Missouri, Nebraska, North Dakota, Ohio, South Dakota, and Wisconsin. Entries provide basic biographical and career information on numerous speakers.